THE INFLUENCE OF THE LEVEL OF PHYSICAL ACTIVITY ON THE BODY MASS INDEX IN STUDENTS FROM CORRENT - PI (Fiep Bulletin - online, 2016)
This study aimed at to investigate the influence of physical activity level (PAL) on body mass index in adolescents in the city of Corrente, Piauí, Brazil. The research sample included 104 students aged between 13 and 19 years, 49 (forty nine) males and 55 (fifty five) females, enrolled in frequent and integrated into the technical high school computer course at the Instituto Federal do Piauí. Students were selected by simple random sampling method and underwent two evaluations: anthropometric (weight, height and IMC) and questionnaire. On the results of analysis of PAL and its relationship with IMC and gender was observed that the average age was 14.92 (± 1.51) years. The anthropometric data for mean height of 1.63 (± 0.05) m and average body mass of 55.15 (± 2.84) kg were observed in BMI classification composed of 25 (24.2%) subjects in the low group weight, 69 (66.2%) in the normal weight group, 10 (9.6%) in the overweight group and 0 (0%) in the obese group.According to the data of the present study we can conclude that the sample participants present prevalence of overweight classification according to IMC variable, with a suggestive area of ??low weight variable in relation to overweight, where no case of obesity was observed in this study. These data might be justified by the influence of sociodemographic characteristics present, below the power level, displacement traversed until the institution of the research, housing and meals. The female group had a higher prevalence physical inactivity, certain predisposition justified by the lack of leisure and physical activity for this population in this age group options. The study shows no correlation of significance compared the variables IMC and physical inactivity.
Keywords: IMC; NAF; Classification; Teenagers.